2003
DOI: 10.1080/08039480310002651
|View full text |Cite
|
Sign up to set email alerts
|

The Danish National Multicenter Schizophrenia Project: Assessment of Psychotic Patients for dynamic Psychotherapy (APPP)

Abstract: Clinicians need guidance in selecting schizophrenic patients for individual psychodynamic psychotherapy. The purpose of the present study was to investigate whether a 17-item questionnaire (APPP) for quantification of suitability for psychotherapy could predict continuance, adherence and outcome from individual dynamic psychotherapy with patients with schizophrenic psychoses. Therapists rated 72 first-episode patients with schizophrenic psychoses in the initial interview. The scores were then correlated to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…In addition, some pretreatment factors were identified as predictors of clinical improvement in psychodynamic psychotherapy for psychoses. These include, in particular, a good therapeutic alliance 42 that can be assessed before treatment is started 43 . Recently, years of psychiatric treatment, number of psychiatric hospitalizations, number of suicide attempts, and the experience of a partnership were found as negative predictors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some pretreatment factors were identified as predictors of clinical improvement in psychodynamic psychotherapy for psychoses. These include, in particular, a good therapeutic alliance 42 that can be assessed before treatment is started 43 . Recently, years of psychiatric treatment, number of psychiatric hospitalizations, number of suicide attempts, and the experience of a partnership were found as negative predictors.…”
Section: Discussionmentioning
confidence: 99%
“…These include, in particular, a good therapeutic alliance 42 that can be assessed before treatment is started. 43 Recently, years of psychiatric treatment, number of psychiatric hospitalizations, number of suicide attempts, and the experience of a partnership were found as negative predictors. Actual work or study activities were found as positive predictors related to clinical improvement in a psychodynamic day treatment program.…”
Section: Threshold From Awareness To Preparation or Rebuilding Phasementioning
confidence: 99%
“…Να επισηµάνουµε εδώ πως έχει καταδειχθεί ότι ειδικά για δυναµικού προσανατολισµού ψυχοθεραπεία, όσον αφορά τους ψυχωτικούς, είναι καλό, για να µειωθεί ο αριθµός των πρόωρα αποχωρήσαντων να διαθέτουν οι ασθενείς: κίνητρο, κατανόηση ανάγκης για ψυχοθεραπεία, ικανότητα µοιράσµατος προσωπικού υλικού, συναισθηµατική επαφή, ιστορικό δηµιουργικότητας, ικανότητα για προσοχή, εναισθησία, ικανότητα ψυχολογικής διαθεσιµότητας, αυτο-παρατηρητικότητα, πρωτοβουλία και ενεργητικότητα, ενδιαφέρον για την άποψη του θεραπευτή, εµπιστοσύνη στον θεραπευτή, και, όσον αφορά την συναισθηµατική κατάσταση και τις συνθήκες αντι-µεταβίβασης του θεραπευτή να εκτιµούνται: η σφαιρική κρίση καταλληλότητας, η έλξη προς τον ασθενή, η κατανόηση του ασθενή, και τα αισθήµατα απελπισίας, ζωντάνιας ή κουράγιου που τυχόν ανακινούν στον θεραπευτή (κλίµακα APPP, Valbak K. et al, 2003).…”
Section: η όρκαunclassified